Pollution characteristics, risk assessment, and environmental associations of microplastics and antibiotic resistance genes in tropical marine aquaculture: A comparative study across different farming systems in Hainan - Yanru Kang; Yongqiang Qin; Nan Chen; Shaobai Wen (Marine Pollution Bulletin, 2026)

Continuous greenhouse tomato cultivation reduces soil microbiome diversity and suppresses beneficial microbial taxa while disturbing nutrient cycling - Xing Liu; Zhuan Zheng; Mengchao Lei; Yanan Cheng; Ying Zhang; Fei Wang; Changwei Shen; Yonggang Li; Bihua Chen (Applied Soil Ecology, 2026)

Microbial network fragmentation at a coal washing hotspot: Assembly mechanisms and stability implications - Senhua Jiang; Yangkun Shi; Jing Zhang; Chenyu Huang; Yue Li; Wenbo Zhang; Jinghui Ma; Nan Chen; Longfei Shu; Cheng Wang; Feifei Liu; Bo Wu (Applied Soil Ecology, 2026)

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Hook development as a non-invasive indicator of sexual maturity in male Procambarus clarkii: Endocrine and molecular insights - Chunyu Hei; Yang Tao; Ruixue Hu; Nan Chen; Jianghua Wang; Zemao Gu (Aquaculture, 2026)

Forest succession enhances vertical stratification of oribatid mite communities between litter and soil layers in subtropical forests - Yuhui Ding; Yannan Chen; Jun Chen (Applied Soil Ecology, 2026)

Soil amendment with biomass-derived carbon dots enhances rhizosphere organic matter, nutrient turnover, and microbial metabolism for maize growth - Yadong Li; Qianying Han; Lihaonan Chen; Shang Lei; Congli Ma; Hongjie Wang (Applied Soil Ecology, 2026)

Soil microplastics pollution can reduce viral abundance and have less consistent impacts on bacteria - Wen-Wen Huang; Yanan Cheng; Dong-Hao Zhou; Quan-Guo Zhang; Hao Yu (Applied Soil Ecology, 2026)

Tree mycorrhizal association types shape oribatid mite communities in a subtropical forest - Yannan Chen; Chenglin Liu; Yu Chen; Xue Pan; Yuhui Ding; Stefan Scheu; Mark Maraun; Jun Chen (Applied Soil Ecology, 2025)

Effects of reproductive condition on haemocyte parameters in the Pacific abalone Haliotis discus hannai during the spawning period - Pantip Sawangwong; Nan Chen; Xuan Luo; Grace Afumwaa Boamah; Jin‐Chywan Gwo; Caihuan Ke; Weiwei You (New Zealand Journal of Marine and Freshwater Research, 2025)
The assessment of morphology and immunology of specimens at different maturity stages is essential for the determination of spawning strategy and reducing the risk of mortality. In this paper, female and male Pacific abalones ( Haliotis discus hannai ) at different statuses (pre‐spawning, spawning and post‐spawning) were collected to estimate the effects of spawning on the immune response. The haemocyte parameters, including total haemocyte counts (THC), haemocyte mortality, and reactive oxygen species production (ROS) were analysed using flow cytometry. THC decreased after spawning, which was lowest 3 days post‐spawning. Haemocyte mortality was higher during spawning, and was highest 3 days post‐spawning. Abalone also reduced their metabolic activity after spawning, reflected by an increase in ROS in both females and males. Moreover, our results show that female abalone reach the spawning period with a higher degree of activities of haemocytes and immune responses than male. The results confirmed that variability in abalone haemocytes during the spawning period might related to individual metabolic conditions.

Effects of soil moisture and vapor pressure deficit on canopy transpiration for two coniferous forests in the Loess Plateau of China - Shengnan Chen; Wei Wei; Bing Tong; Liding Chen (Agricultural and Forest Meteorology, 2023)

Fish type I and type II interferons: composition, receptor usage, production and function - Zhen Gan; Shan Nan Chen; Bei Huang; Jun Zou; Pin Nie (Reviews in Aquaculture, 2020)
Interferons ( IFN s) have been reported in vertebrates from fish to mammals. To date, two types of IFN s, i.e. type I and type II IFN s have been reported in a range of fish species in aquaculture. In fish, type I IFN s are clarified into group I and group II , with two cysteines and four cysteines, and further into subgroups a, d, e, h, and b, c, f, respectively. Group I IFN s appear to exist in all fish species, whereas group II IFN s are discovered only in certain species such as cyprinids, salmonids and perciform fish. It seems preferentially functional that group I IFN s signal through cytokine receptor family B ( CRFB ) 5 and CRFB 1, while group II IFN s through CRFB 5 and CRFB 2. But they all initiate a same signalling pathway for the expression of interferon induced genes. The information about the production and the function of type I IFN s in fish are further summarized in the review. Interestingly, two members of type II IFN s, IFN ‐γ and a unique member, IFN ‐γ related gene ( IFN ‐γrel) exist in fish, and IFN ‐γ and IFN ‐γrel can separately become homodimers for signalling through CRFB 13, CRFB 17, CRFB 6 and CRFB 17, respectively. In addition, the variation in the composition of type I and type II IFN s as well as in their receptors in some cyprinid and salmonid fish has also been reviewed. It is suggested that future perspectives for the research on type I and type II IFN s in fish are outlined from a comparative and evolutionary point of view.